Some Notes of the Fractional Integral and Derivatives and Its Applications - Fen Qin; Fuyi Xu; Huizeng Qin (Journal of Mathematics)
In this paper, the definitions of the fractional derivative and integrals are given by the neutrix limit. Not only is it consistent with the classical results but also the representations of the fractional derivative and integrals are obtained for x−a−k, x−a−klnpx−a, x−a−kfx, and x−a−klnpx−afx, where k,p=1,2,…,fx is the analytic function.